Ending overcriminalization and mass incarceration : hope from civil society / Anthony B. Bradley. - Bradley, Anthony B., 1971- (Cambridge University Press, 2018)
Mass incarceration is an overwhelming problem and reforms are often difficult, leading to confusion about what to do and where to start. Ending Overcriminalization and Mass Incarceration: Hope from Civil Society introduces the key issues that need immediate attention and provides concrete direction about effective solutions systemically and relationally. In this work Anthony B. Bradley recognizes that offenders are persons with inherent dignity. Mass incarceration results from the systemic breakdown of criminal law procedure and broken communities. Using the principle of personalism, attention is drawn to those areas that directly contact the lives of offenders and determine their fate. Bradley explains how reform must be built from the person up, and once these areas are reformed our law enforcement culture will change for the better. Taking an innovative approach, Anthony B. Bradley explores what civic institutions need to do to prevent people from falling into the criminal justice system and recidivism for those released from prison.